Gouw Peng Liang's Lo Fen Koei text (1903) as a cultural practice of the Chinese peranakan community: A new historicism study - Susanto, Dwi (citeus, 2023)
Lo Fen Koei text (1903) by Gouw Peng Liang has been neglected in the history of Indonesian literature due to the numerous discourses on power and social, political, and ideological issues that flourished at the time. The objective of this study is to discover about the text's active response to social, political, and other discourses that exist outside of its existence. The issues addressed in this study are (1) the historical context and author's stance, (2) the meaning of Lo Fen Koei's (1903) text, and (3) the texts and discourse around Lo Fen Koei's (1903) text. The study uses a New Historicism persfective. The Loe Fen Koei text (1903) as a material object and the text's cultural practices as a formal object are the objects of this study. The study data include contents and ideas of Lo Fen Koei text (1903), the social setting in which the text is situated, non-literary texts that are present at the same time, and diverse information related to the topic. Data interpretation techniques were used to prove the paratext corresponding to the Lo Fen Koei text (1903) by following procedures presented in New Historicism studies such as reading the meaning of the text, linking the meaning of the text or the presence of the text with the social situation and discourse that developed at the time. The results of this paper reveal that Lo Fen Koei text (1903) by Gouw Peng Liang has relevance to cultural practices within Chinese society in responding to diverse prevalent discourses. Meanwhile, the vision and objective of the Tiong Hua Hwee Kuan (THHK) cultural organization, the recinanization movement or Khong Hucu, and opposing to colonial policies exist as evidence of cultural practice. This text was a proponent of cultural nationalism and the restoration of noble teachings. Through the concepts of liberalism and westernization, the work also addressed on the practice of colonialism in the colonial time.